Fixation, description and DNA barcode of a neotype for Botryllus schlosseri (Pallas, 1766) (Tunicata, Ascidiacea) - Brunetti, Riccardo; Manni, Lucia; Mastrototaro, Francesco; Gissi, Carmela; Gasparini, Fabio (Zootaxa, 2017)
Botryllus schlosseri is a widespread colonial ascidian commonly considered cosmopolitan and amply used as model for researches ranging from developmental biology to immunobiology. Recently, molecular data lead to hypothesize that the species named B. schlosseri may consist of more than a single taxon. Indeed, five highly divergent clades, named A-E, have been genetically identified and are referred as cryptic species. In this context, and lacking both a type and a detailed morphological description, we believe that it is necessary, as a taxonomic reference point, to designate a neotype and re-describe the species. Therefore, a sample from the Lagoon of Venice (Adriatic Sea, Italy) was deposited as neotype in the Natural History Museum of Venice (Italy), preserved both in formalin and in 90% ethanol. Here we provide a morphological description of the suggested neotype of B. schlosseri that takes into account several developmental stages (oozooid, zooid of first blastogenic generations, and mature zooid) and is carefully compared with the previous descriptions of samples coming from other European and non-European localities. Finally, we associate our morphological description to a “DNA barcode”, consisting in a long fragment of the mitochondrial COI gene. Our description is associated to clade A, although at now we cannot guarantee that this association is univocal.